The effects of the duration of mobile phone use on heart rate variability parameters in healthy subjects - Ekici, Berkay (Anatol J Cardiol, 2016)
OBJECTIVE: This study aimed to estimate the influence of the duration of mobile phone use on heart rate variability (HRV) in healthy individuals. METHODS: One hundred forty-eight individuals without any established systemic disease and who had undergone 24-h ambulatory ECG monitoring were included in the case-control study. All the individuals had been using mobile phones for more than 10 years. Three-channel 24-h Holter monitoring was performed to derive the mean heart rate, standard deviation of normal NN intervals (SDNN), standard deviation of 5-min (m) mean NN intervals (SDANN), the proportion of NN50 divided by the total number of NNs (pNN50), the root mean square differences of successive NN intervals (RMSSD), high (HF)-, low (LF)-, very low (VLF)-frequency power, total power components, and the LF/HF ratio. Individuals were divided into four groups according to their duration of mobile phone use [no mobile phone use (Control group), <30 min/day (Group 1), 30–60 min/day (Group 2), and >60 min/day (Group 3)]. RESULTS: All the groups had similar features with regard to demographic and clinical characteristics. No significant arrhythmias were observed in any of the groups. The LF/HF ratio was higher, whereas the SDNN, SDANN, RMSSD, and pNN50 values were lower in the study groups than in the control group (p<0.05). No significant differences were identified among groups with respect to heart rate, VLF, and total power values (p>0.05). CONCLUSION: In this study, it was shown that the duration of mobile phone use may affect the autonomic balance in healthy subjects. The electromagnetic field created by mobile phone use may induce HRV changes in the long term.